The applications of epigallocatechin gallate (EGCG)-nanogold conjugate in cancer therapy. (13th March 2023) - Karimi-Shahri, Mehdi; Alalikhan, Abbas; Hashemian, Pedram; Hashemzadeh, Alireza; Javid, Hossein
Abstract: Cancer has recently increased the death toll worldwide owing to inadequate therapy and decreased drug bioavailability. Long-term and untargeted chemotherapeutic exposure causes toxicity to healthy cells and drug resistance. These challenges necessitate the development of new methods to increase drug efficacy. Nanotechnology is an emerging field in the engineering of new drug delivery platforms. The phytochemical epigallocatechin gallate (EGCG), the main component of green tea extract and its most bioactive component, offers novel approaches to cancer cell eradication. The current review focuses on the nanogold-based carriers containing EGCG, with an emphasis on the chemotherapeutic effects of EGCG in cancer treatment. The nanoscale vehicle may improve the EGCG solubility and bioavailability while overcoming constraints and cellular barriers. This article reviewed the phytochemical EGCG-based gold nanoplatforms and their major anticancer applications, both individually, and in combination therapy in a few cases.